Computer-assisted audit tools in verification tasks: Implementation in Microsoft Excel and in CaseWare IDEA - Laureano, Raul M. S.; Pedrosa, I. (Actas de la 11a Conferencia Ibérica de Sistemas y Tecnologías de Información, 2016)
Business analytics is an information system that combines different data from internal and external sources from organizations in order to help to improve the knowledge of the managers, as well as the decision making process. The competitive advantage is created by better and greater understanding of the data. It focuses on business and gathers three types of analysis: descriptive, predictive and prescriptive. This study aims to propose a framework that can guide companies in the implementation of business analytics solutions. Moreover, it aims to identify a set of critical success factors that can increase the probability of a successful implementation of the system. The framework and the critical success factors are validated through semi-structured interviews with experts in business analytics, working in the information technology industry. The results let us propose a framework with five stages and the identification of 18 critical success factors. This study allows to expand the knowledge that managers have of business analytics and its implementation, allowing the organization to create value and therefore a competitive advantage. No contexto profissional de contabilistas e auditores a necessidade de realização de tarefas de verificação de coerência dos dados é recorrente. Assim, estão disponíveis no mercado, aplicações destinadas a esses procedimentos, tal como, o CaseWare IDEA, sendo que as mesmas são anunciadas como possuindo interface simples e amigável com o utilizador. Adicionalmente, outras aplicações de uso geral, como o Microsoft Excel, permitem executar a verificação de dados, sendo que alguns alertas podem, no caso do Excel, ser associados à funcionalidade de formatação condicional. Há, na utilização de cada uma das ferramentas mencionadas, algum desconhecimento sobre as potencialidades, aspeto esse que se pretende endereçar no decurso deste trabalho, nomeadamente, no estabelecimento da comparação entre uma ferramenta de utilização geral e outra específica na realização de tarefas de verificação e deteção de fraude.